A comparative experimental and theoretical study on the structural and optical properties of ZnO synthesized at room temperature using an ultrasonication technique. Issue 1 (24th August 2022) - Malik, Khurshaid Ahmad; Malik, Javied Hamid; Assadullah, Insaaf; Bhat, Aadil Ahmad; Tomar, Radha
Abstract: In the present article we report a comparative experimental and theoretical study on the structural and optical properties of ZnO. First principle calculations were carried out using density functional theory (DFT) to study the electronic structure of ZnO. The direct‐type band gap was found in the ZnO's typical estimated energy band structure in the Brillouin zone path G‐G or in the middle of the Γ k‐point grid. To develop UV/ZnO/O2 /H2 O2 system for photodegradation of organic contaminants in an aqueous system, zinc oxide (ZnO) nanostructures were synthesized using an ultrasonication process at ambient temperature. To test the photocatalytic activity of synthesized nanostructures, we used phenol red (PR) dye as a test substrate. We found that ZnO nanostructures photo‐degraded PR dye at a rate of over 90% under ultraviolet light irradiation, converting photonic energy into chemical energy (photocatalytic energy conversion) that can be used for water purification. To explore the structural, optical, morphological, and compositional characteristics of synthesized ZnO nanostructures, various techniques including powder X‐ray diffraction, Fourier‐transform infrared spectroscopy, UV‐visible spectroscopy, scanning electron microscopy, and energy dispersive X‐ray spectroscopy were used. Abstract :